IMPLEMENTASI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN OLEH PT.BINTARA TANI NUSANTARA DI KECAMATAN RANAH BATAHAN KABUPATEN PASAMAN BARAT - ,, Abd Rahmad (Normative Jurnal Ilmiah Hukum, 2022)
Social and Environmental Responsibility in Indonesia is regulated in Law No. 40 of 2007 concerning Limited Liability Companies. As stated in Article 74 paragraph (1), it states that 'Companies that carry out their business activities in the field and/or related to natural resources are obliged to carry out Social and Environmental Responsibilities'. PT. BintaraTani Nusantara is one of the Regional Owned Enterprises that was established in 1984 which is engaged in the plantation and management of oil palm. The formulation of the problem in this paper is 1) how is the implementation of social and environmental responsibility carried out by PT. Bintara Tani Nusantara in the District of Ranah Batahan, 2) what are the factors that become obstacles for PT. Bintara Tani Nusantara in implementing social and environmental responsibility in the District of Ranah Opinions and solutions to resolve obstacles. The research method is sociological juridical, the nature of the research is descriptive and the data used are primary data and secondary data obtained through interviews and literature studies, then processed by editing, coding, and tabulating processes.Dataanalysis with a qualitative approach. The results of the research on the application of social and environmental responsibility carried out by PT. Bintara Tani Nusantara to the community in the Ranah Batahan sub-district, namely by carrying out a programmed Social and Environmental Responsibility program which is budgeted annually according to the management policy of PT. Bintara Tani Nusantara. In addition, the non-programmed Social and Environmental Responsibility program is also implemented by PT. Bintara Tani Nusantara. The obstacle for PT. Bintara Tani Nusantara in implementing Social and Environmental Responsibility in the Ranah Batahan sub-district is internal factors and external factors.